The Nuremberg military tribunals and the origins of international criminal law - Heller, Kevin Jon. (Oxford : Oxford University Press, 2011)
Less famous than the Nuremberg International Military Tribunal but no less important, the Nuremberg Military Tribunals tried lower-level functionaries and private citizens for their parts in WWII. This text gives a full overview of these trials and it traces the critical role they have played in the development of international criminal law.
Description based on print version record.
Includes bibliographical references and index.
Keywords: International criminal law; Nuremberg War Crime Trials, Nuremberg, Germany, 1946-1949.